Disaster risk perception and preparedness of households in Yangon, Myanmar: Disaster experiences, socio-demographic factors and spatial variation - Zin Mar Than; Hlaing Maw Oo; Toe Aung; Tin Tin Kyi; Saw Sandar Oo; Win Lei Mar; Willkomm, Marlene; Miller, Christian; Martini, Stefan; Zin Nwe Myint; Khin Khin Soe; Win Maung; et al. (ERDKUNDE, 2023)
In disaster-prone countries, it is of great concern that societies as a whole, as well as households and individuals, should become as resilient to disasters as possible. In Myanmar, with its frequent natural hazards like floods, cyclones and droughts and its high probability of earthquakes, raising awareness of and preparedness for disasters is of eminent importance in order to increase the resilience of society, households and individuals. Disaster research shows that the awareness and perception of people regarding disasters and thus also their risk preparedness can vary substantially. This seems to stem from various sources: the socio-demographic characteristics of households and people as well as former experiences of disaster seem to play a crucial role. Information of such variables and understanding how they influence the disaster risk perception and preparedness of households and people can provide an important background against which to improve individual disaster risk awareness and preparedness – with the final aim of making society, households and individuals more resilient. In this paper, the results of a household survey carried out in eight townships of Yangon (Myanmar) are presented. The analysis investigates how socio-demographic characteristics and the previous experiences of disaster of the respondents and their households influence their disaster risk perception and preparedness in different areas of Yangon City. The results show strong differences in disaster risk perception and preparedness according to socio-demographic characteristics and previous experiences of disaster in different areas of Yangon City. Finally, the findings feed into and inform about successful disaster management.